Physical activity on prescription for children with obesity: a focus group study exploring experiences in paediatric healthcare - Boman, Charlotte; Bernhardsson, Susanne; Lundqvist, Stefan; Melin, Karin; Lauruschkus, Katarina (Frontiers in Health Services, 2024)
Background Insufficient physical activity is a growing public health concern and is closely linked to obesity in both adults and children. Swedish physical activity on prescription (PAP) is effective in increasing physical activity levels in adults, but knowledge about how PAP is used in paediatric healthcare is lacking. Therefore, this study aimed to explore experiences of working with PAP for children with obesity amongst paediatric staff and managers. Methods Seven focus group discussions with 26 participants from paediatric outpatient clinics in western Sweden were conducted. Data were analysed both inductively and deductively, framed by the Normalization Process Theory's four core constructs: coherence, cognitive participation, collective action, and reflexive monitoring. Results The PAP work for children with obesity was experienced to be about helping children to become physically active, and less about losing weight. Identified barriers for using PAP were the non-uniform nature of the work and a perceived lack of guidelines. Collaboration with physiotherapists and physical activity organisers outside the organisation was identified as an important facilitator. An important contextual factor for implementing PAP is the collaboration between paediatric clinics and physical activity organisers. In the transition between these stakeholders, maintaining a family-centred approach when working with PAP was experienced as challenging. Conclusions PAP is a well-known intervention that is inconsistently used for children with obesity. The intervention should include a family-centred approach for this patient group. It also needs to align better with existing collaborations with other healthcare units as well as with new forms of collaboration with physical activity organisers in the community.